Web-Based Waste Reporting Application Analysis in Dinas Lingkungan Hidup Kabupaten Kampar - Khairul Azhar; Deddy Gusman; Hanantatur Adeswastoto (Journal of Engineering Science and Technology Management (JES-TM), 2022)
At this time the application of information technology has grown rapidly, not only on website-based technology but also mobile-based technology. The use of cellular phones is increasingly widespread among the public, people as cellular phone users can use their cellular phones for various needs, including being able to complain to the government, one of which is reporting waste. Garbage can have a negative impact on health if not handled, thus a more effective way is needed to improve communication between the community and the government regarding waste reports. Therefore, a web-based waste reporting application will be made using the PHP programming language and the MYSQL database, with the methodology used in designing this system using the RUP method. The advantage in the website-based waste reporting application is that it can make it easier for the public to report waste and the Dinas Lingkungan Hidup Kabupaten Kampar can find out the locations of the waste piles reported by the community.